2015
DOI: 10.1186/s12875-015-0331-9
|View full text |Cite
|
Sign up to set email alerts
|

Access to healthcare for long-term conditions in women involved in street-based prostitution: a qualitative study

Abstract: BackgroundWomen involved in street-based prostitution (SBP) have well-documented health problems specific to their occupation, but access to care for other chronic health problems has not been explored. Primary care is seen as the optimal context to deliver care for people with long-term conditions because it is accessible, efficient, and can tackle inequalities related to socioeconomic deprivation. We aimed to explore the perspectives of women involved in SBP about access to health care for their long-term co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
0
17
0
5
Order By: Relevance
“…Evidence exists that CSWs are at heightened risk of ill health (Mastrocola et al, 2015), substance misuse and violence (Deering et al, 2014), during crisis situations as they become frustrated and sometimes depressed. Leaders of some CSWs groups in the study area have criticized the Government's lack of action to protect their health and social needs during the pandemic since they held the perception that the government was just insensitive to their needs at this crucial time that their livelihood has been significantly affected by the pandemic and its associated restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists that CSWs are at heightened risk of ill health (Mastrocola et al, 2015), substance misuse and violence (Deering et al, 2014), during crisis situations as they become frustrated and sometimes depressed. Leaders of some CSWs groups in the study area have criticized the Government's lack of action to protect their health and social needs during the pandemic since they held the perception that the government was just insensitive to their needs at this crucial time that their livelihood has been significantly affected by the pandemic and its associated restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Sex workers are at heightened risk of ill health,1 substance misuse, and violence,2 said the ECP, and unless the services they rely on resume normal operation soon and sex workers’ financial hardship is tackled, their health problems will multiply.…”
mentioning
confidence: 99%
“…'Fund outreach programmes to help often excluded groups such as those with mental health problems, learning disabilities and the homeless to access general practice.' Few women in our study 10 reflected positively on relationships with general practice, or described an ongoing therapeutic relationship with one supportive GP. Primary care was failing these women.…”
Section: Continuity Of Care Commissioning and The Third Sectormentioning
confidence: 95%
“…2 Women involved in SBP also suffer physical, as well as the better documented psychosocial, comorbidities. 10 We reported that women involved in SBP have poor knowledge of their physical conditions and how to optimally manage them. Their chaotic lifestyle, and limited perceptions of the seriousness of their health problems, resulted in help-seeking at a time of crisis and often resorting to the use of unscheduled care.…”
mentioning
confidence: 99%